Morality and politics in modern Europe : the Harvard lectures - Oakeshott, Michael, 1901-1990 (Oakeshott, Michael, 1901-1990. Works. 1993., 1993)
When Michael Oakeshott, Britain's leading twentieth-century political philosopher, died in 1990, he left a substantial collection of unpublished material, including fully elaborated essays and complete full-length manuscripts. Yale University Press now makes available selected items from these illuminating works.In Morality and Politics in Modern Europe, Oakeshott argues that two conflicting moralities underlie two opposed understandings of the office of government in modern Europe. On one hand is the morality of individuality, according to which the role of government is to frame and enforce rules of law that enable individuals to invent and pursue in peace their own diverse projects. On the other is the morality of collectivism, by which government is interpreted as the manager of a unified enterprise whose function is to provide for the community, regarded as an organic whole that pursues a single project to which all other activities are subordinate. The book, based on a series of eight lectures delivered at Harvard University in 1958, contains new material of great interest to students of Oakeshott's thought and of the history of political theory in general. There is, for example, a substantial interpretation of Locke and discussions of Kant, Adam Smith, Edmund Burke, Jeremy Bentham, and J.S. Mill. Introduced by Shirley Robin Letwin, who attended the lectures, the book provides a compact introduction to ideas that Oakeshott developed more elaborately in other writings.